Disrupting assumptions about graduate employability: exploring culturally and linguistically diverse university students' graduate capitals in Australia. Issue 2 (4th March 2023) - Baker, Sally; Xavier, Anna; Due, Clemence; Dunwoodie, Karen; Newman, Alex
ABSTRACT: Employability is a powerful discourse in higher education, yet as a driver for policy and practice it has not translated into an uplift in graduate outcomes for all student groups. In particular, Culturally and Linguistically Diverse Migrant and/or Refugee (CALDMR) students experience inequitable graduate outcomes and access to meaningful employment opportunities. Drawing on a national study of career advisors and CALDMR students' experiences of how Australian universities support their career development, we examine CALDMR students' employability through the conceptual framework of graduate capitals. We make two key contributions: firstly, we offer insights into staff and student perceptions of university approaches with CALDMR. Secondly, we identify a lack of linguistic and cultural diversity conceptualisations of employability by examining the experiences of CALDMR students and staff through the lens of graduate capitals. We disrupt the assumptions and presumed familiarity with cultural knowledge.